Participation Rate as A Basis for Measuring Food Security Status of Meat - Soedjana, Tjeppy D (Indonesian Animal Sciences Society, 2013)
Food security has been developed as way for decision makers to pay more attention to this sector. It is believed that foods which are efficiently produced in one area or country may be accessed by other areas or countries. However, this concept is difficult to be implemented since almost none of countries in the world have all resources to produce what is needed by its people. Food consumption, including beef, would be better measured using participation rate which indicates a cluster of its consumer instead of using all population as a denominator for calculating per capita consumption, except for commodities whose consumer member of its cluster close to 100% of the population. For commodities whose consumers less than 50% of its cluster it is more effective to use the size of the cluster as the denominator. Diversified food consumption of animal origin in Indonesia has been indicated by the fact that it has been naturally established. Animal meat consumption diversification for many reasons is influenced by cultural, preferences or other economic status of the households. This phenomena is also indicated by the magnitude of positive cross price elasticity between beef and mutton, beef and poultry meat, and between poultry meat and fish. Therefore, every effort to push higher consumption of one meat type, will reduce the participation rate of others. Susenas data indicated participation rates for beef and buffalo meat were 26.15% (2002), 21.93% (2005), 16.18% (2008) and 16.16% (2011), while poultry meat had higher participation rate as 65.46% (2002), 63.48% (2005), 57.67% (2008) and 56.98% (2011). Application of participation rate approach on the production of beef and buffalo meat resulted in the annual percapita consumption of 6.71 kg (2002), 10.47 kg (2005), 10.82 kg (2008) and 13.11 kg (2011). It concludes that balanced participation rates of meat components (beef and poultry meat), need to be maintained as the existed diversified meat consumption. Effort to increase beef consumption will result in deindustrialization to other meat. Key words: Participation rate, food security, food diversification, meat